The Influence of English Language Learning on the Development of Civic Character among Students in the English Language Education Study Program at Nusa Cendana University - Kezya Arete Rosamor Ndoen; Grandy Abraham Matatula; Lilis Stasya Atabunanim; Lionel Alfa Nuban Dearlovemarch Tuthaes; Greis Evalinda; Alfret Benu (Peneliti.net, 2026)
This study aims to analyze the influence of English language learning on the development of civic character among students in the English Language Education Study Program, Universitas Nusa Cendana. The methods used include interviews and observations over a period of two weeks, involving lecturers and students as sources of information. This study shows a positive influence of English language learning on the development of civic character among students. Through the learning process, students not only master the language but also gain insight into various principles of democracy, human rights, and cultural diversity. Collaborative activities in learning, such as discussions and presentations, also contribute to shaping their sense of responsibility and active engagement. Nevertheless, challenges arise from the negative influence of foreign culture, which sometimes threatens national values. Therefore, the development of a critical attitude and the cultivation of strong civic values are needed so that students are able to adapt in the era of globalization without losing their national identity. This study recommends the integration of civic values into the English language learning curriculum to create a younger generation with civic character and a global perspective.